2017
DOI: 10.1093/jamia/ocx065
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a scalable, web-based, automated clinical decision support risk-prediction tool for chronic kidney disease using C-CDA and application programming interfaces

Abstract: We validated the use of interoperable documents and open-source components to develop a low-cost tool for automated clinical decision support. Since Consolidated Clinical Document Architecture-based data extraction extends to any certified EHR, this demonstrates a successful modular approach to clinical decision support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In addition, regarding utilization of ANN and CNN methods, Kolachalama et al [76] recently provided a perspicacity into the association of pathological fibrosis identified from histologic images with clinical phenotypes for patients with CKD, helping the diagnostics and prognostics of these phenotypes. Subsequently, there has been an increasing number of AI studies, with great emphasis on the usage of nephrology and transplantation [85,[87][88][89]. Inspired by the idea of mimicking the biological structure of human brains, deep learning is a subfield of machine learning based on ANN [74].…”
Section: Using Electronic Health Record Data In Nephrologymentioning
confidence: 99%
“…In addition, regarding utilization of ANN and CNN methods, Kolachalama et al [76] recently provided a perspicacity into the association of pathological fibrosis identified from histologic images with clinical phenotypes for patients with CKD, helping the diagnostics and prognostics of these phenotypes. Subsequently, there has been an increasing number of AI studies, with great emphasis on the usage of nephrology and transplantation [85,[87][88][89]. Inspired by the idea of mimicking the biological structure of human brains, deep learning is a subfield of machine learning based on ANN [74].…”
Section: Using Electronic Health Record Data In Nephrologymentioning
confidence: 99%
“…A recent study showed that an automated laboratory‐based CDSS might help to improve physician adherence to guidelines regarding timely monitoring of CKD . Samal et al . have built a modern web‐based CDSS to calculate the risk of kidney failure and display it for CKD patients, and the inputs of the system are real‐time patient data.…”
Section: Application Of Big Data In Nephrologymentioning
confidence: 99%
“…34 A recent study showed that an automated laboratory-based CDSS might help to improve physician adherence to guidelines regarding timely monitoring of CKD. 35 Samal et al 36 have built a modern web-based CDSS to calculate the risk of kidney failure and display it for CKD patients, and the inputs of the system are real-time patient data. However, the sample sizes of aforementioned studies cannot satisfy the "volume" of big data, and the representativeness of samples in those studies needs to be verified.…”
Section: Risk Prediction and Clinical Decision Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a project where we extracted numeric estimated glomerular filtration rates and numeric urine albumin‐to‐creatinine ratios, our laboratory information system output nonstandard text strings for “>60” and “Below Assay”(Samal et al. ).…”
mentioning
confidence: 99%